Proyecto de factibilidad para la implementación de una cooperativa de transporte escolar en el cantón Francisco de Orellana, para el año 2015 - Peralta Montesdeoca, Santiago (2016)
The objective of this thesis is to develop a feasibility project for the implementation of a School Transportation Cooperative in the Canton Francisco de Orellana, by 2015. The present thesis was developed according to an established schedule, in which methods and research techniques such as the Deductive Method, the Inductive Method, the Statistical Method and the Analytical Method were used, as well as the use of bibliographic materials, surveys and virtual material. In the market study carried out in the canton Francisco de Orellana, with a sample of 377 families and 1 Transport School company; Tabulated the surveys have been analyzed and the results have been inferred to then carry out the market analysis, determining the Potential Demand of 5,185 families, Real Demand 2,437 families, Effective Demand 1,048 families, which determine that they use 217,974 school transportation services. The Offer of 110,500 school transportation services and the Unsatisfied Demand of 107,484 school transportation services. The installed capacity of the project determines that the company will be able to offer 95,040 school transportation services and the capacity used will be 85,536 school transportation services. Likewise, an administrative study was carried out, determining as a Limited Liability Company, and with the functional organizational structure at the hierarchical levels, both Legislative, Executive, Adviser Level, Support Level, Operational Level, as well as function manuals, organizational charts. The project achieves an investment of $ 118,754.36 and 15.79 per cent of the total investment of $ 18,754.36 will be financed by partners and a loan to be maintained by the National Finance Corporation will constitute the 84.21% corresponding to 100,000.00 dollars to 10 years term at 15% annual interest. The financial evaluation presents the following results: according to the NPV of the present project gives us a positive value of 2,113.45 dollars, indicating that the project or investment is convenient. For the present project, the IRR is 15.47%, this being a satisfactory value to carry out the project, the time required to recover the original investment would be 4 years, 2 months and 24 days, for the present project, the sensitivity values Are less than one, therefore changes in costs and revenues increased by 10% and decreased by 4%, respectively, ie the project is not sensitive to these changes.